Angioembolization as a life-saving maneuver for unstable pelvic fractures in skeletally immature children: a multicenter case series - Zhang, Mao; Du, Dingyuan; Du, Gongliang; Yu, Anyong; Fu, Yong; Luo, Yong; Guo, Junhua; Yi, Yunfeng; Huang, Guangbin; Li, Hui (Frontiers in Pediatrics, 2025)
BackgroundHemodynamically unstable pelvic fractures (HUPF) in skeletally immature children and adolescents carry significant mortality. While internal iliac artery embolization (IIAE) is a cornerstone of management for HUPF in adults, data on its application and outcomes in this truly pediatric population, particularly in China, are scarce. This study aimed to evaluate the feasibility, safety, and clinical outcomes of IIAE for HUPF in this specific, vulnerable group.MethodsThis multicenter, retrospective case series included patients aged 15 years or younger who presented with HUPF and underwent IIAE at three major Chinese trauma centers between 2019 and 2023. Key outcomes included immediate hemorrhage control, in-hospital mortality, and long-term complications.ResultsA total of seven patients underwent IIAE. The cohort demonstrated severe trauma, with a median Pelvic Abbreviated Injury Scale (AIS) of 5 and a median Injury Severity Score (ISS) of 36. Of the six patients who underwent contrast-enhanced computed tomography (CECT), active arterial extravasation was identified in four. However, subsequent angiography confirmed life-threatening arterial injuries in all seven patients, including the two with negative CECT scans. Immediate and sustained hemodynamic stability was achieved in six patients (85.7%). The single mortality occurred in a patient with refractory hemorrhagic shock who required a massive transfusion of 28.5 units of red blood cells, whereas the median for the six survivors was 4 units. At a median follow-up of 22 months, all survivors were ambulatory and no major procedure-related ischemic complications were observed.ConclusionIIAE is a feasible and effective life-saving intervention for HUPF in skeletally immature patients. A negative CECT scan does not rule out significant arterial injury, underscoring the vital role of prompt angiography. We recommend a low threshold for early intervention, with consideration of non-selective embolization as a primary damage control tactic in these critically injured children.